2017
DOI: 10.1038/cdd.2017.43
|View full text |Cite
|
Sign up to set email alerts
|

Caspase involvement in autophagy

Abstract: Caspases are a family of cysteine proteases widely known as the principal mediators of the apoptotic cell death response, but considerably less so as the contributors to the regulation of pathways outside cellular demise. In regards to autophagy, the modulatory roles of caspases have only recently begun to be adequately described. In contrast to apoptosis, autophagy promotes cell survival by providing energy and nutrients through the lysosomal degradation of cytoplasmic constituents. Under basal conditions aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
119
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 120 publications
5
119
0
1
Order By: Relevance
“…We have not identified the mechanism by which exercise improves tolerance to ischemia and attenuates the tissue renal damage caused by ischemia‐reperfusion injury. However, moderate aerobic exercise decreases the development of cardiovascular diseases such as hypertension, helps control cholesterol and weight, preserves bone mass, improves glucose, oxygen and nutrient uptake into skeletal muscle, increases respiratory capacity and ATP (Guimarães et al ; Zhu et al ; Tsapras and Nezis, ). We suggest the better physical conditioning of trained animals may lead to better hemodynamic and metabolic conditions, and finally, cellular and molecular survival mechanisms of renal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…We have not identified the mechanism by which exercise improves tolerance to ischemia and attenuates the tissue renal damage caused by ischemia‐reperfusion injury. However, moderate aerobic exercise decreases the development of cardiovascular diseases such as hypertension, helps control cholesterol and weight, preserves bone mass, improves glucose, oxygen and nutrient uptake into skeletal muscle, increases respiratory capacity and ATP (Guimarães et al ; Zhu et al ; Tsapras and Nezis, ). We suggest the better physical conditioning of trained animals may lead to better hemodynamic and metabolic conditions, and finally, cellular and molecular survival mechanisms of renal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The latter view is supported by studies showing that autophagy inhibition may decrease apoptosis [33]. Under basal conditions autophagy and apoptosis cross-regulate each other through an elaborate network of interconnections which also includes the interplay between autophagy-related proteins (ATGs) and caspases [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Apart from apoptosis, CaspaseTracker could potentially also be activated during alternative types of cell death as cells can switch cell death pathways during their course that directly or indirectly involves caspase activation, such as autophagy after starvation 95,96 , necrosis by the cold shock-induced plasma membrane rupture 19,55,56,78 , and staurosporine-induced necroptosis 97,98 . Our present and previous studies demonstrated that the CaspaseTracker biosensors can label cells recovered from these cell death inductions in vitro or in vivo 17,18,19,20,21 .…”
Section: Discussionmentioning
confidence: 99%